78.3k views
1 vote
Tiana solved the equation

-2(3x - 5) = 4(x + 3) + 8. When
she double checked her work
by substituting, it made the
equation untrue.

User Dodinas
by
5.2k points

1 Answer

2 votes

Answer:

actually when I solved it ,the equation is true

Explanation:

look

-2 (3x - 5) = 4(x + 3) + 8

-6x + 10 = 4x + 12 + 8

-6x + 10 = 4x + 20

-6x - 4x = 20- 10

-10x = 10

x = -1

and when I substitute, I get 16 on both sides so I don't know where the problem is

User VigneshK
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.